Marine Environment Protection and Biodiversity Conservation - Roberts, Julian. author. aut Link
XXI, 289 p. 16 illus.
Keywords: Despite the potential benefits that PSSA designation can deliver, recent practice both within the IMO and by individual member States, has considerably undermined confidence in this emerging concept. The focus of this book is on the events within the IMO that have led to this lack of confidence arising. In doing so, this book presents an examination of coastal State practice with the PSSA concept. In undertaking this analysis, the research provides evidence of the value of the PSSA concept, but also demonstrates its limitations. In this regard, the book presents a ‘reality check’ which seeks to rationalise some of the heightened expectations with the concept that are apparent in the current debate. The research argues that States may seek to designate PSSAs more for their ‘iconic status’ than for any demonstrable environmental benefits that may be realised.